(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the issues of integrating the results of foreign scientific expeditions organized in the Turkestan region in 1867–1917 into modern socio-humanitarian research and applied fields. The article reveals the importance of geographical, ethnographic, cartographic and statistical data collected during the expeditions in the development of modern history, sociology, anthropology, tourism and digital humanities. It also indicates the main problems in implementing this scientific heritage into practice - the closed or underutilized use of archival materials, translation problems, the slowness of the digitization process and the lack of interdisciplinary research. The article provides practical proposals and recommendations on digitizing the materials of Turkestan scientific expeditions, creating historical maps based on GIS technologies, creating international scientific databases, and introducing them into the fields of education and tourism. The study substantiates the need to harmonize scientific heritage with the needs of modern science and society